Development and implementation of a technical and didactical training program for student tutors in the dissection course - Shiozawa, Thomas; Hirt, Bernhard; Celebi, Nora; Baur, Friederike; Weyrich, Peter; Lammerding-Köppel, Maria (Annals of anatomy, 2010)
Student tutors have a long tradition in gross anatomy instruction. However, the full potential of the tutors is generally not tapped, since little attention is paid to their technical and didactical training. The aim of this paper is to report a systematic approach to the development, didactic reasoning and implementation of a curriculum for training student tutors in gross anatomy. The training program was developed using the six-step approach of Kern's curriculum development model. For needs assessment, the literature research was amended by a survey among the 1st and 2nd year students of the dissection course ( n = 167) and two independent 90 min focus group interviews with the tutors who supervised these students ( n = 15). Protocols were transcribed and analyzed by margin coding. The training curriculum was setup on the basis of these data. Corresponding to the literature, the students want student tutors with good teaching competence as well as adequate content knowledge and technical competence. Supporting that, the tutors request a training program enhancing their didactic skills as well as their knowledge of content and working using relevant methods. Thus, a combined didactic and professional training program has been developed. Six professional and 11 didactic learning objectives were defined. A 3 weeks training curriculum was implemented, using microteaching and group exercises for didactics and active dissection for technical training. Both parts were interlocked on a contextual and practical level. Our focus group analyses revealed that a specific training program for student tutors in the dissection course is necessary. We describe a feasible task-oriented training curriculum combining didactic and professional objectives.